Validation of the AUSGeoid98 model in Western Australia using historic astrogeodetically observed deviations of the vertical - Featherstone, Will; Morgan, L. (Royal Society of Western Australia, 2007)
AUSGeoid98 is the national standard quasigeoid model of Australia, which is accompanied by a grid of vertical deviations (angular differences between the Earth's gravity vector and the surface-normal to the reference ellipsoid). Conventionally, co-located Global Positioning System (GPS) and spirit-levelling data have been used to assess the precision of quasigeoid models. Here, we instead use a totally independent set of 435 vertical deviations, observed at astrogeodetic stations across Western Australia before 1966, to assess the AUSGeoid98 gravimetrically modelled vertical deviations. This point-wise comparison shows that (after three-sigma rejection of 15 outliers) AUSGeoid98 can deliver vertical deviations with a precision (standard deviation) of around one arc-second, which is generally adequate for the reduction of current terrestrial-geodetic survey data in this State.